2019
DOI: 10.2147/cmar.s176938
|View full text |Cite
|
Sign up to set email alerts
|

FOXN2 is downregulated in breast cancer and regulates migration, invasion, and epithelial–mesenchymal transition through regulation of SLUG

Abstract: IntroductionForkhead box (FOX) N2 (FOXN2), a member of FOX protein family, has been reported to play critical roles in some types of cancers. However, the expression and function of FOXN2 in breast cancer remain unclear.MethodsIn the present work, we explored the detailed molecular mechanism of FOXN2 in breast cancer. We performed RT-qPCR and Western blotting analysis to detect the expression of FOXN2 in breast cancer. Colony formation assay, CCK-8 assay, wound healing assay, and Transwell assay were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Our study is the first to reveal the possible relationship between HOXC6/miR-188-5p and FOXN2 in cell migration. A previous study showed that FOXN2 may be associated with cell cycle regulation, proliferation, and DNA damage response [ 33 ], suggesting that FOXN2 may be associated with the expression of genes related to these pathways. We will be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to reveal the possible relationship between HOXC6/miR-188-5p and FOXN2 in cell migration. A previous study showed that FOXN2 may be associated with cell cycle regulation, proliferation, and DNA damage response [ 33 ], suggesting that FOXN2 may be associated with the expression of genes related to these pathways. We will be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…15 FOXN4 is a tumor suppressor in breast cancer through inhibition of slug. 16 Importantly, FOXN4 is a key regulator in a variety of biological processes during development. However, little is known about the function of FOXN4 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 was further shown to be induced by TGFβ in kidney cells undergoing EMT, where it was demonstrated to play a significant role (147). Although the Forkhead box transcription factors as discussed above have been shown to regulate EMT in a positive manner, a few of the members of the family, such as FOXF2, FOXN2 and FOXO3a have been found to act as EMT suppressor (148)(149)(150)(151). FOXF2 has been shown to be a negative regulator of EMT in basal-like breast cancer cells and also in triple negative breast cancer cells.…”
Section: Forkhead Box Family Of Transcriptionmentioning
confidence: 99%
“…Moreover, FOXF2 was shown to recruit nuclear receptor corepressor 1 (NCoR1) and histone deacetylase 3 (HDAC3) to the FOXQ1 promoter to repress its transcription. FOXN2, on the other hand, repressed Slug expression by binding to its promoter directly and thereby inhibiting its transcription (149). FOXO3a, another member of the Forkhead box family, has been reported to play a negative regulatory role during EMT in prostate cancer cells.…”
Section: Forkhead Box Family Of Transcriptionmentioning
confidence: 99%